Empowerment of Women Weavers as MSME Actors in Kupang Regency: Analysis of Challenges and Effective Strategies - Hamka, ‎; Pancawati, Galuh; Ginting, Karnida Retta (KnE Social Sciences, 2025)
This research article aims to determine women’s empowerment through MSMEs to overcome poverty in Kupang Regency, and strategies to overcome factors that hinder the effectiveness of empowerment. This study uses a qualitative approach with data collection methods through structured interviews, FGDs, and secondary data documentation. The results of the study indicate that 1) Women’s empowerment by the local government through MSMEs has not fully met the expectations of weavers because local government intervention is still limited. 2) The causes of this failure are economic factors and low competency development. 3) The strategy is directed at strengthening capital, developing expertise in information technology, improving product quality, and marketing. These efforts are carried out through management and access to capital, technical guidance, and supervision of the quality of woven products. For this reason, collaboration is needed between local governments, craftsmen, and cooperatives/private parties in encouraging increased productivity, product quality, and marketing. The role of local governments is very important in facilitating craftsmen through empowerment policies that are relevant to their needs and expectations, and encouraging the private sector/cooperatives to support local government policies to improve the welfare of weavers. Further research is needed on the implementation of empowerment policies that involve all stakeholders.